Molecular Profiling of Exceptional Responders to Cancer Therapy. (28th November 2020) - Bilusic, Marijo; Girardi, Daniel; Zhou, Yan; Jung, Kyungsuk; Pei, Jianming; Slifker, Michael; Chen, Qingrong; Meerzaman, Daoud; Alpaugh, Katherine; Young, Denise; Flieder, Douglas; Gray, Phillip; et al.
Abstract: Background: The vast majority of metastatic cancers cannot be cured. Palliative treatment may relieve disease symptoms by stopping or slowing cancer growth and may prolong patients' lives, but almost all patients will inevitably develop disease progression after initial response. However, for reasons that are not fully understood, a very few patients will have extraordinary durable responses to standard anticancer treatments. Materials and Methods: We analyzed exceptional responders treated at Fox Chase Cancer Center between September 2009 and November 2017. An exceptional response was defined as a complete response lasting more than 1 year or a partial response or stable disease for more than 2 years. Tumor samples were analyzed using an Ambry Genetics test kit with a 142‐gene panel. Messenger RNA expression was evaluated using NanoString's nCounter PanCancer Pathways Panel and Immune Profiling Panel and compared with matched controls for gender, age, and cancer type. Results: Twenty‐six exceptional responders with metastatic bladder, kidney, breast, lung, ovarian, uterine, and colon cancers were enrolled. Mutations were identified in 45 genes. The most common mutation was an EPHA5 nonsynonymous mutation detected in 87.5% of patients. Mutations in DNA damage repair pathway genes were also frequent, suggesting increased genome instability. We also found varying expression of 73 genes in the Pathways panel and 85 genes in the Immune Profiling panel, many of them responsible for improvement in tumor recognition and antitumor immune response. Conclusions: The genomic instability detected in our exceptional responders, plus treatment with DNA damage compounds combined with favorable anticancer immunity, may have contributed to exceptional responses to standard anticancer therapies in the patients studied. Implications for Practice: With recent advances in the treatment of cancer, there is increased emphasis on the importance of identifying molecular markers to predict treatment outcomes, thereby allowing precision oncology. In this study, it was hypothesized that there is a "specific biologic signature" in the biology of the cancer in long‐term survivors that allows sensitivity to systemic therapy and durability of response. Results showed that DNA damage repair pathway alterations, combined with favorable anticancer immunity, may have contributed to exceptional responses. It is very likely that an in‐depth examination of outlier responses will become a standard component of drug development in the future. Abstract : Some patients with metastatic cancer will have markedly better responses to treatment than other patients receiving the same treatment. These exceptional responders are not often studied. This article reports the results of a single‐center study that aimed to identify specific molecular signatures among exceptional responders and to unravel molecular patterns that could explain how exceptional responders beat the odds.